2016
DOI: 10.1097/md.0000000000003814
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of Intraoperative Dexmedetomidine on Postoperative Pain in Highly Nicotine-Dependent Patients After Thoracic Surgery

Abstract: To investigate the effects of intraoperative dexmedetomidine on pain in highly nicotine-dependent patients after thoracic surgery.Highly nicotine-dependent men underwent thoracic surgery and received postoperative patient-controlled intravenous analgesia with sufentanil. In dexmedetomidine group (experimental group, n = 46), dexmedetomidine was given at a loading dose of 1 μg/kg for 10 minutes, followed by continuous infusion at 0.5 μg/kg/h until 30 minutes before the end of surgery. The saline group (control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 22 publications
(25 reference statements)
1
21
0
Order By: Relevance
“…The remaining 11 publications were screened by reading the full text. One article [23] was excluded because dexmedetomidine for intraoperative anesthesia, rather than for postoperative PCA. One article [24] was excluded because only the abstract was provided in English; another article was excluded because it described an ongoingstudy and only provided a summary.…”
Section: Resultsmentioning
confidence: 99%
“…The remaining 11 publications were screened by reading the full text. One article [23] was excluded because dexmedetomidine for intraoperative anesthesia, rather than for postoperative PCA. One article [24] was excluded because only the abstract was provided in English; another article was excluded because it described an ongoingstudy and only provided a summary.…”
Section: Resultsmentioning
confidence: 99%
“…In the study literature. [ 6 ], the mean ± SD morphine consumption for 48 h with and without dexmedetomidine were 35 ± 28 and 54 ± 37 mg, respectively, a 41% reduction of morphine use with dexmedetomidine. In our study, the hypothesis was that compared with control group, dexmedetomidine group would achieve a 30% reduction of sufentanil consumption.…”
Section: Methodsmentioning
confidence: 99%
“…Some studies report that perioperative and postoperative systemic usage of dexmedetomidine provides considerably more satisfactory analgesic effect, reduces PCA morphine requirements and lower incidence of postoperative side effects compared to morphine alone [ 4 6 ]. Compared with morphine, sufentanil improve immediate postoperative pain control with a strong analgesic effect; however, because patients undergoing complex thoracotomy may be continue to experience respiratory depression and increase the incidence of other complications, an adjunct drug such as dexmedetomidine, has been suggested as a safe alternative to together with sufentanil by way of patient-controlled intravenous analgesia (PCIA) [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“… 24 One study reported that dexmedetomidine led to a decreased requirement for opioid analgesics and inhaled anesthetics, and lessened the incidence of severe changes of circulation during traumatic phases of surgeries. 25 Forty-six thoracic surgery patients given dexmedetomidine at a loading dose of 1 μg/kg for 10 min, followed by continuous infusion at 0.5 μg/kg/h until 30 min before the end of surgery, exhibited reduced resting and coughing numerical rating scale scores and a sufentanil-sparing effect during the first 24 h. 26 Premedication with a single intravenous dose of 0.5 μg/kg dexmedetomidine decreased the intraoperative propofol and postoperative analgesic requirements, and increased the postoperative satisfaction and Ramsay sedation scale scores considerably in patients undergoing direct laryngoscopic biopsy under total intravenous anesthesia. 27 In an analysis of 364 patients from seven intermediate- to high-quality randomized controlled trials, it was found that sensory block duration was prolonged by at least 34%, motor block duration was prolonged by at least 17%, and time to first analgesic request was increased by at least 53% when intravenous dexmedetomidine was administered with spinal anesthesia.…”
Section: Effect Of Intraoperative Dexmedetomidine On Perioperative Pamentioning
confidence: 99%